Réponses

2013-05-05T12:20:46+02:00

A= 6x-(5x+4)

= x-4

 

B= 7(3x+4)-6

= 21x+22

 

C= (x-4)(2x-5)

= 2x²-3x+20

 

D= (2x+5)(3x-1)+5(x-2)

=6x²+22x-5

2013-05-05T12:23:02+02:00

A = 6x - (5x + 4)

A = 6x - 5x - 4

A = x - 4

 

 

B = 7 (3x + 4 ) - 6

B =  21x + 28 - 6

B = 21x + 22

 

 

C= ( x - 4 ) ( 2x - 5 ) 

C = 2x² - 5x - 8x + 20 

C = 2x² - 13x + 20

 

D = (2x + 5 ) ( 3x - 1 ) + 5 ( x - 2 )

D = 6x² - 2x + 15x - 5  + 5 ( x - 2 )

D = 6x² - 2x + 15x - 5  + 5x -10

D = 6x² + 18x - 15 

 

 

et voila :) si tu comprends pas regarde jtai mis les étapes pour faire les calculs :)